Advances in the molecular pathogenesis and cell therapy of stress urinary incontinence - Wang, Xiao-xiao; Zhang, Lei; Lu, Ye (Frontiers in Cell and Developmental Biology, 2023)
Stress urinary incontinence (SUI) is very common in women. It affects patients’ mental and physical health, and imposed huge socioeconomic pressure. The therapeutic effect of conservative treatment is limited, and depends heavily on patient persistence and compliance. Surgical treatment often brings procedure-related adverse complications and higher costs for patients. Therefore, it is necessary to better understand the potential molecular mechanisms underlying SUI and develop new treatment methods. Although some progress has been made in the basic research in recent years, the specific molecular pathogenic mechanisms of SUI are still unclear. Here, we reviewed the published studies on the molecular mechanisms associated with nerves, urethral muscles, periurethral connective tissue and hormones in the pathogenesis of SUI. In addition, we provide an update on the recent progresses in research on the use of cell therapy for treating SUI, including research on stem cells therapy, exosome differentiation and gene regulation.